Letter from Richard Adolf Zsigmondy to Georg Bredig, October 1905 - Zsigmondy, Richard Adolf (1905)
In a letter to Georg Bredig (1868-1944), the Austrian chemist, Richard Adolf Zsigmondy (1865-1929), discusses his recent work in the field of colloidal chemistry. In 1925, Zsigmondy was awarded the Nobel Prize in chemistry in 1925 for co-inventing the slit-ultramicroscope.
Keywords: Nobel Prize winners; Bredig, Georg, 1868-1944; Zsigmondy, Richard Adolf, 1865-1929